The Paradox Of Artificial Intelligence In Learning: The Existence Of Technology And The Challenges Of Critical Thinking For High School Students - Surviyana, Surviyana; Nuryani, Pupun (DAS CONFERENCE INTERNATIONAL SERIES, 2026)
This article examines the paradox of Artificial Intelligence (AI) in learning, focusing on the coexistence of technological advancement and the challenges it poses to students' critical thinking at the senior high school level. The study aims to critically analyze how AI is positioned in learning practices and how its use influences students' cognitive processes and critical thinking skills. This research employs a qualitative approach through a literature study (library research), analyzing books, scientific journals, and relevant scholarly publications that discuss AI in education, critical thinking, and contemporary pedagogy. The findings indicate that AI has become a dominant entity in students' learning practices, particularly in completing academic tasks. AI is widely perceived as an efficient and practical tool that provides instant answers and reduces cognitive effort. However, this convenience simultaneously contributes to a shift in learning orientation from knowledge construction to answer consumption. The study reveals a tendency toward cognitive offloading, reduced analytical engagement, and the weakening of epistemic processes such as evaluation, reflection, and argumentation. These conditions illustrate a pedagogical paradox: while AI holds potential as cognitive scaffolding, its unregulated use often substitutes students' reasoning rather than supporting it. The study concludes that the core challenge of AI in education lies not in the technology itself, but in the absence of reflective pedagogical design. Without clear instructional strategies and critical mediation by teachers, AI risks reinforcing instrumental rationality and surface learning. Therefore, this research underscores the need for pedagogical frameworks that position AI as a medium for critical dialogue, metacognitive reflection, and meaningful learning, ensuring its alignment with the fundamental goals of education.